2015
DOI: 10.1042/cs20150405
|View full text |Cite
|
Sign up to set email alerts
|

The balance between IL-17 and IL-22 produced by liver-infiltrating T-helper cells critically controls NASH development in mice

Abstract: The mechanisms responsible for the evolution of steatosis towards NASH (non-alcoholic steatohepatitis) and fibrosis are not completely defined. In the present study we evaluated the role of CD4(+) T-helper (Th) cells in this process. We analysed the infiltration of different subsets of CD4(+) Th cells in C57BL/6 mice fed on a MCD (methionine choline-deficient) diet, which is a model reproducing all phases of human NASH progression. There was an increase in Th17 cells at the beginning of NASH development and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
153
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(176 citation statements)
references
References 39 publications
10
153
0
Order By: Relevance
“…In this study, WT mice were fed an MCD diet for 8 weeks, subsequently developed NASH with fibrosis, and were shown to have increased infiltration of T helper 17 (Th17) and T helper 22 (Th22) cells, which play a role in inflammation 29 . Infiltration of Th17 cells increased at both the beginning of the development of NASH and at the transition to NASH with fibrosis, and there was increased infiltration of Th22 cells between these two phases 29 . Considering that NAFL (which presents with little to no fibrosis) can progress to NASH with significant fibrosis 30 , this association between inflammation, inflammatory cell infiltration and hepatic fibrosis development gives important insight into the pathophysiology of these diseases.…”
Section: Methionine- and Choline-deficient (Mcd) Dietmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, WT mice were fed an MCD diet for 8 weeks, subsequently developed NASH with fibrosis, and were shown to have increased infiltration of T helper 17 (Th17) and T helper 22 (Th22) cells, which play a role in inflammation 29 . Infiltration of Th17 cells increased at both the beginning of the development of NASH and at the transition to NASH with fibrosis, and there was increased infiltration of Th22 cells between these two phases 29 . Considering that NAFL (which presents with little to no fibrosis) can progress to NASH with significant fibrosis 30 , this association between inflammation, inflammatory cell infiltration and hepatic fibrosis development gives important insight into the pathophysiology of these diseases.…”
Section: Methionine- and Choline-deficient (Mcd) Dietmentioning
confidence: 99%
“…In a study by Rolla et al the authors examined the role of hepatic inflammation in the development of NASH with fibrosis in the MCD diet mouse model 29 . In this study, WT mice were fed an MCD diet for 8 weeks, subsequently developed NASH with fibrosis, and were shown to have increased infiltration of T helper 17 (Th17) and T helper 22 (Th22) cells, which play a role in inflammation 29 .…”
Section: Methionine- and Choline-deficient (Mcd) Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous researches provided evidence for the hepatoprotective role of IL-22 in liver damage [17,18]. In animal models of non-alcoholic steatohepatitis (NASH) IL-22 alone exerted hepatoprotective activity, but this effect was lost in the presence of IL-17 [19]. On the other hand, the study of Wu et al has shown that IL-22 alone was involved in the stimulation of hepatic fibrogenesis [20].…”
Section: Introductionmentioning
confidence: 91%